Exploring the Impact of Psycholinguistic Strategies on Vocabulary Retention Among English Learners - Ithriyah, Siti (Zona Education Indonesia, 2024)
This study explores the impact of psycholinguistic strategies on vocabulary retention among United Kingdom language learners. Using the pretest-posttest experimental method, 60 participants with intermediate levels of United Kingdom language proficiency were divided into two groups: experimental and control. The experimental group received instruction using psycholinguistic strategies such as semantic maps, contextual learning, and spaced repetition, while the control group used traditional memorization methods. The results showed that the experimental group experienced a significant improvement in vocabulary retention, both immediately after the intervention and one month later. Statistical analysis confirmed that psycholinguistic strategies are more effective than traditional methods in improving long-term retention. In addition, qualitative data showed that participants in the experimental group felt more engaged and understood vocabulary better. This study concludes that psycholinguistic strategies can improve the effectiveness of vocabulary teaching by supporting natural cognitive processes in language learning. These findings provide important insights for United Kingdom educators to integrate psycholinguistic approaches in vocabulary teaching to achieve better learning outcomes